Correlation of Total Eosinophils in peripheral blood with bronchoprovocative testing with acetylcholine in patients with bronhchial asthma - Dimitrievska, Deska; Zdraveska, Marija; Gjorcev A; Todevski D; Janeva E; Vlashki, Emilija (My University, 2015)
The main attributes of asthma are airway obstruction, spontaneous or treatment induced reversibility, increased bronchial reactivity to exogenous and endogenous stimuli (triggers) and inflammation of the tracheobronchial tree. Since the basic characteristic of asthma is airway hyper reactivity, proving the existence of airway reactivity can make valid diagnosis. The airway hyperactivity is caused by airflow inflammation. Nevertheless, the markers of asthmatic inflammation can also be present in peripheral blood. Two methods for detection of airway inflammation were used in this study, PC20 to methacholine bronchoprovocation and eosinophyl (Eo) count, ECP and IL-5 in peripheral blood. We estimated their correlation. This study includes 30 asthmatic patients of the Pulmology and Allergy Clinic, Skopje, Macedonia. In all of the patients Eo count, ECP and IL-5 in peripheral blood and PC20 to methacholine bronchoprovocation were followed at the beginning of the study, after 2 and 6 months. The results show statistically significant correlation (p<0.05) between markers of inflammation in peripheral blood and PC20 to methacholine. Our conclusion is that each of the evaluated markers may be used in the diagnosis of asthma, alone or in combination. The inflammatory markers in peripheral blood can be used as a screening method in the management of asthma as well as a diagnostic parameter for asthma, especially in cases when bronchoprovocative tests can not be performed.
Keywords: bronchial asthma; diagnosis; Eo count; PC20 to acetylcholine